Deregulation of E-cadherin, β-catenin, APC and Caveolin-1 expression occurs in canine prostate cancer and metastatic processes. (June 2018) - Kobayashi, Priscila E.; Fonseca-Alves, Carlos E.; Rivera-Calderón, Luis G.; Carvalho, Márcio; Kuasne, Hellen; Rogatto, Silvia R.; Laufer-Amorim, Renée
Abstract: Prostate cancer is a heterogeneous disease with high levels of clinical and gene heterogeneity, consequently offering several targets for therapy. Dogs with naturally occurring prostate cancer are useful models for molecular investigations and studying new treatment efficacy. Three genes and proteins associated with the WNT pathway (β-catenin, APC and E-cadherin) and Caveolin-1 (CAV-1) were evaluated in canine pre-neoplastic proliferative inflammatory atrophy (PIA), prostate cancer and metastatic disease. The APC gene methylation status was also investigated. As in human prostate cancer, cytoplasmic and nuclear β-catenin, which are fundamental for activating the canonical WNT pathway, were found in canine prostate cancer and metastasis. Membranous E-cadherin was also lost in these lesions, allowing cellular migration to the stroma and nuclear localization of β-catenin. In contrast to human prostate tumours, no APC downregulation or hypermethylation was found in canine prostate cancer. The CAV-1 gene and protein overexpression were found in canine prostate cancer, and as in humans, the highest levels were found in Gleason scores ≥8. In conclusion, as with human prostate cancer, β-catenin and E-cadherin in the WNT pathway, as well as Caveolin-1, are molecular drivers in canine prostate cancer. These findings provide additional evidence that dogs are useful models for studying new therapeutic targets in prostate cancer. Highlights: Loss of membranous E-cadherin and β-catenin expression occurred in canine prostate cancer. Different from humans, APC promoter methylation was not observed in canine prostate cancer (PC) samples. Increased CAV-1 gene and protein expression was found in canine prostate cancer.